INNOVATIVE METHODS OF TEACHING PRE-INTERMEDIATE LEVEL STUDENTS - Khaitova, Alokhon Ilyosbek kizi (Innovative Development in Educational Activities, 2024)
The article includes various information about the methods of teching pre-intermediate level students and benefits and challenges while teaching as well as the measures to be taken.